Post Abortion Choice and Acceptance of Contraception - Shrestha, Ashis; Sharma, P (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: This study was conducted to find out choice and acceptance of contraceptives in clients coming for first trimester abortion. Methods: This was a cross sectional descriptive study carried out from the records of clients who received comprehensive abortion care service in first trimester at Kasthamandap health care centre from June 2008 to June 2010. Results: Total 707 clients came for abortion who fulfilled inclusion criteria. Contraceptive acceptance was 49.5%. Most frequently used contraceptives were injectable (depot medroxyprogesterone) 22.8%, oral contraceptive pills 19.6%, condom 6.1%, intra-uterine contraceptive device 0.8% and norplant 0.3%. Conclusions: This study showed a low acceptance rate of contraception. This suggests the need for reviewing the policy of post abortion contraception. The study also highlighted that depot provera was the most accepted contraception. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 14-17 DOI: http://dx.doi.org/10.3126/njog.v8i1.8854